Application of SSF-FWS constructed wetland system for landfill leachate treatment - Ain Nihla, Kamarudzaman; Johan, Sohaili, Prof. Madya Dr.; Mohd. Faizal, A. J. (Universiti Teknologi Malaysia (UTM), 2011)
2nd International Conference and Workshops on Basic and Applied Sciences and Regional Annual Fundamental Science Seminar (ICORAFSS) 2009 organized by Universiti Teknologi Malaysia, from 2nd - 4th June 2009 at Johor Bahru, Johor, Malaysia.